Effects of a group-based music imagery program on promoting coping resources among undergraduate students: a pilot randomized controlled trial - Cheng, Winnie Lai Sheung; Wong, Lokki Lok-Ki (Frontiers in Psychology, 2023)
Background: Music is well-known for its stress-reducing effects. Little is known about the potential effect of music interventions in fostering internal coping resources for stress management among undergraduate students in Hong Kong.Objectives: This pilot study aimed to examine the efficacy of the Group-based Focus Music Imagery Program (GFMI) in promoting a stress-is-enhancing mindset, sense of coherence, and self-compassion among undergraduate students.We used a two-arm parallel randomized controlled trial (RCT). The experimental arm received 6 weeks of GFMI with measures taken at two time points after completing baseline assessments (Weeks 6, 10). The control arm received 6 weeks of an active control program and completed the outcome measures at time points similar to the GFMI group.